2020
DOI: 10.7759/cureus.11086
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Blood Transfusion in Percutaneous Nephrolithotomy

Abstract: Introduction Percutaneous nephrolithotomy (PNL) has replaced open surgery for the treatment of kidney stones due to its less invasive nature. Bleeding still occurs due to renal vascular injuries, dependent upon the access route of the procedure. Several other factors are also related to the increased risk of bleeding. This study aims to find the association between blood transfusion and other factors such as age, gender, body mass index (BMI), size of the stone, operative time, preoperative hemoglobin (Hb) lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…However, transfusion remains the most common and serious complication. In our study, we identi ed 5.85% patients receiving PCNL need transfusion, which was higher with occurrence rates of UK (2.5%) [21] and USA (1.3%) [22], while lower than other Asian countries (18.3%, 23.1%) [23,24]. This may suggest that the relationship of the transfusion rate in PCNL varied between Asian and Western populations, and it is crucial to establish risk prediction models.…”
Section: Discussionmentioning
confidence: 70%
“…However, transfusion remains the most common and serious complication. In our study, we identi ed 5.85% patients receiving PCNL need transfusion, which was higher with occurrence rates of UK (2.5%) [21] and USA (1.3%) [22], while lower than other Asian countries (18.3%, 23.1%) [23,24]. This may suggest that the relationship of the transfusion rate in PCNL varied between Asian and Western populations, and it is crucial to establish risk prediction models.…”
Section: Discussionmentioning
confidence: 70%
“…В таких случаях необходимо проведение Кт-ангиографии, с последующей эмболизацией кровоточащего сосуда [151]. Неудачная пункция, единственная оставшаяся почка, удвоенная почка, множественные камни, длительная операция, инфекция мочевыводящих путей, инфекционные камни и сахарный диабет считаются факторами риска послеоперационных геморрагических осложнений [152][153][154][155]. Несмотря на то, что анатомичная пункция почки является важным этапом, чрезмерное усилие на инструменте при нефроскопии может привести к разрыву почки, увеличивая риск кровотечения.…”
Section: осложненияunclassified
“…Kim et al found that correct renal puncture was a significant risk factor for severe hemorrhage requiring angioembolization (27). Ullah et al reported that operating time, female gender, and stone size were the main risk factors (28).…”
Section: Postoperative Large Hematomamentioning
confidence: 99%